Agronomy explains large yield gaps in smallholder oil palm fields - Monzon, Juan Pablo (2023)
The role of agronomic management for explaining yield gaps in smallholder oil palm fields has received little attention.• We assessed yield gaps in smallholder oil palm fields using a crop model, survey data, and field measurements.• Average farmer yield was low, representing 42% of the attainable yield as determined by local weather and soil.• Among management practices, nutrients, harvest interval, weeds control, and pruning have largest influence on yield gaps.• Improving agronomic management can increase smallholders oil palm yield and profit on existing plantation area.